The influence of engine speed upon pre-ignition - Goodger, E. M. (College of Aeronautics, 1956)
The literature shows conflicting evidence on the effect of engine speed upon tendency to pre-ignition. Typical published results are presented and compared, together with results obtained from a single-cylinder D.V.L. engine at Cranfield, using the heated wire and ionization gap technique. The D.V.L. results show an initial increase in pre-ignition tendency with increase in engine speed, followed by a reduced tendency with further increase in speed, and are thus similar to certain other published results. The D.V.L. results are less detailed than these published results, since no measurement was made of hot-spot temperatures, but are more extensive since a greater number of fuels was tested for speed effect, and pre-ignition tendency with speed was measured over a range of (reduced) inlet pressure.